Metal paste for joining, and joint body and method for producing the same
Patent Information
- Application Number
- JP2023124665
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-31
- Publication Date
- 2025-02-13
AI Technical Summary
【0011】 本発明によれば、PEGを含有しながらも、、高湿環境下であっても溶媒分離が発生しにくい接合用金属ペースト、それを用いる接合体の製造方法及び接合体を提供することができる。
Smart Images

Figure 2025020997000004 
Figure 2025020997000005 
Figure 2025020997000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal paste for bonding, a bonded body, and a method for producing the same. [Background technology]
[0002] When manufacturing semiconductor devices, various bonding materials are used to form a bonding layer that bonds a semiconductor element to a lead frame or the like (supporting member). For example, high-lead solder has been used to form a bonding layer for bonding power semiconductors, LSIs, and the like that operate at temperatures up to about 150°C. In recent years, semiconductor elements have become higher capacity and more space-saving, and there is an increasing demand for semiconductors to operate at high temperatures of 175°C or higher. In order to ensure the operational stability of such semiconductor devices, the bonding layer needs to have high connection reliability and high thermal conductivity. However, in the temperature range of 175°C and above, the bonding layer of the high-lead solder that has been used traditionally has problems with connection reliability and has insufficient thermal conductivity (30 Wm -1 K -1 ) therefore alternative materials are needed.
[0003] As one of the alternative materials, a sintered silver layer formed by the sintering phenomenon of silver particles has been proposed (see Patent Document 1 below). Sintered silver layers have high thermal conductivity (>100 Wm -1 K -1 ), which has been reported to have high connection reliability against power cycles, has attracted attention (see Non-Patent Document 1 below). However, to ensure connection reliability, a thermocompression process accompanied by high pressure is essential to improve the density of the sintered silver layer, which poses problems such as damage to semiconductor element chips and reduced throughput in the thermocompression process. Another problem is that silver is expensive as a material.
[0004] As another alternative material, a sintered copper layer using copper has been proposed. Copper has superior mechanical strength compared to silver, and high-temperature reliability can be easily obtained without increasing the density as much as in the case of a sintered silver layer, and material costs can also be kept low. As such a sintered copper layer, a sintered copper layer obtained by reducing and sintering copper oxide particles has been proposed (see Patent Document 2 and Non-Patent Document 2 below). In this case, a reducing agent may be used in combination from the viewpoint of easily removing the oxide film of the copper particles and the adherend to proceed with sintering while maintaining the metal surface (producing a metallic bond). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 4247800 [Patent Document 2] Patent No. 5006081 [Non-patent literature]
[0006] [Non-Patent Document 1] R. Khazaka, L. Mendizabal, D. Henry: J. ElecTron. Mater, 43(7), 2014, 2459-2466 [Non-Patent Document 2] T. Morita, Y. Yasuda: Materials Transactions, 56(6), 2015, 878-882 Summary of the Invention [Problem to be solved by the invention]
[0007] The inventors have discovered that metal pastes containing polyethylene glycol (PEG) as a reducing agent have the property that PEG functions as a highly polar solvent and can exert a reducing effect at the heating temperature of the metal paste, making it easy to ensure sufficient sinterability. However, they are prone to solvent separation (precipitation) in high humidity environments.
[0008] In general, when joining members via a sintered metal layer, a metal paste containing metal particles and a dispersion medium is dispersed and applied to one of the members by a printing method. The working environment is controlled as required, but it may be an open system. If solvent separation occurs due to a high humidity environment during storage of the metal paste, during dispersion treatment, during application, or after application, it may lead to poor printing, poor appearance of the coating film, or reduced sinterability.
[0009] Therefore, an object of the present invention is to provide a metal bonding paste which contains PEG but is resistant to solvent separation even in a high humidity environment, a method for producing a bonded body using the same, and a bonded body. [Means for solving the problem]
[0010] The present invention relates to the following [1] to [8]. [1] A metal paste for bonding containing metal particles, a dispersion medium, and a reducing agent, the reducing agent being polyethylene glycol, and the compound A having, within its molecule, at least one group selected from the group consisting of an amino group, a carboxyl group, and an acetylene group, and a hydroxyl group. [2] The metal paste for bonding according to [1], wherein the metal particles are surface-treated with a fatty acid having 12 to 18 carbon atoms. [3] The metal paste for joining according to [1] or [2], wherein the compound A includes at least one selected from the group consisting of triethanolamine, diethanolamine, monoethanolamine, hydroxyacetic acid, and acetylene alcohol surfactants. [4] The metal paste for bonding described in any one of [1] to [3], wherein the metal particles include sub-micro copper particles having a volume average particle size of 0.01 μm or more and 0.8 μm or less, and micro copper particles having a volume average particle size of 2 μm or more and 50 μm or less. [5] The bonding metal paste according to [4], wherein the micro copper particles are flake-shaped. [6] A method for manufacturing a joined body, comprising: a step of preparing a laminate in which a first member, a metal paste for joining according to any one of [1] to [5], and a second member are laminated in this order; and a step of sintering the metal paste for joining in the laminate. [7] The method for producing a bonded body according to [6], wherein at least one of the first member and the second member is a semiconductor element. [8] A joined body comprising: a first member, a second member, and a sintered body of the joining metal paste according to any one of [1] to [5] that joins the first member and the second member. Effect of the Invention
[0011] According to the present invention, it is possible to provide a metal bonding paste which contains PEG but is resistant to solvent separation even in a high humidity environment, a method for producing a bonded body using the same, and a bonded body.
[0012] Furthermore, the metal bonding paste of the present invention can suppress aggregation of metal particles even when prepared in a high humidity environment, and can have sufficient printability. [Brief description of the drawings]
[0013] [Figure 1] 1 is a schematic cross-sectional view showing an example of a bonded body produced using the bonding metal paste of the present embodiment. [Diagram 2] 1 is a schematic cross-sectional view showing an example of a bonded body produced using the bonding metal paste of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to the following embodiments.
[0015] <Metal paste for bonding> The bonding metal paste of the present embodiment includes metal particles, a dispersion medium, and a reducing agent. The bonding metal paste includes polyethylene glycol as a reducing agent, and also includes a compound A having, in a molecule thereof, at least one group selected from the group consisting of an amino group, a carboxyl group, and an acetylene group, and a hydroxyl group.
[0016] According to the bonding metal paste of the present embodiment, even though it contains polyethylene glycol as a reducing agent, it is possible to suppress the occurrence of solvent separation even in a high humidity environment. The present inventors speculate as follows about the reason for obtaining such an effect. First, the present inventors believe that the cause of the occurrence of solvent separation in a high humidity environment is that the water-absorbed PEG repels the metal particles and precipitates. In contrast, it is considered that the incorporation of compound A allows the water-absorbed PEG to have affinity with the surface of the metal particles via compound A, making it difficult to precipitate.
[0017] [Metal particles] Examples of the metal particles according to the present embodiment include copper particles such as submicro copper particles and micro copper particles, and metal particles other than these copper particles.
[0018] The copper particles include submicro copper particles and micro copper particles. The copper particles refer to particles containing copper as a main component, for example, particles having a copper content of 80% by mass or more. The copper content of the copper particles may be 85% by mass or more, 90% by mass or more, 95% by mass or more, 99% by mass or more, or 100% by mass.
[0019] (Submicron copper particles) The sub-micro copper particles may be copper particles having sinterability in a temperature range of 250°C to 380°C. Examples of the sub-micro copper particles include copper particles having a particle size of 0.01 μm to 0.8 μm. For example, copper particles having a volume average particle size of 0.01 μm to 0.8 μm can be used. If the volume average particle size of the sub-micro copper particles is 0.01 μm or more, effects such as reduction in the synthesis cost of the sub-micro copper particles, good dispersibility, and reduction in the amount of organic protective agent used can be easily obtained. If the volume average particle size of the sub-micro copper particles is 0.8 μm or less, the effect of excellent sinterability of the sub-micro copper particles can be easily obtained. From the viewpoint of further achieving the above effect, the volume average particle size of the sub-micro copper particles may be 0.6 μm or less, 0.5 μm or less, or 0.4 μm or less. In addition, the volume average particle size of the sub-micro copper particles may be 0.02 μm or more, 0.05 μm or more, or 0.1 μm or more. The volume average particle size of the sub-micro copper particles may be, for example, 0.01 μm or more and 0.5 μm or less, 0.12 μm or more and 0.8 μm or less, 0.15 μm or more and 0.8 μm or less, 0.15 μm or more and 0.6 μm or less, 0.2 μm or more and 0.5 μm or less, or 0.3 μm or more and 0.45 μm or less.
[0020] In this specification, the volume average particle size means a 50% volume average particle size. When determining the volume average particle size of copper particles, the copper particles as raw material or dried copper particles obtained by removing volatile components from a bonding metal paste are dispersed in a dispersion medium using a dispersant, and the volume average particle size can be determined by a method of measuring the dispersion medium using a light scattering particle size distribution measuring device (for example, Shimadzu nanoparticle size distribution measuring device (SALD-7500nano, manufactured by Shimadzu Corporation)). When using a light scattering particle size distribution measuring device, hexane, toluene, α-terpineol, 4-methyl-1,3-dioxolan-2-one, water, etc. can be used as the dispersion medium.
[0021] The content of the submicro copper particles may be 20% by mass or more, 30% by mass or more, 35% by mass or more, 40% by mass or more, 90% by mass or less, 85% by mass or less, 80% by mass or less, 20% by mass or more and 90% by mass or less, 30% by mass or more and 90% by mass or less, 35% by mass or more and 85% by mass or less, or 40% by mass or more and 80% by mass or less, based on the total mass of the metal particles. If the content of the submicro copper particles is within the above range, it is easy to ensure the bonding strength of the bonded body produced by sintering the bonding copper paste, and when the bonding copper paste is used for bonding a semiconductor element, the semiconductor device tends to exhibit good die shear strength and connection reliability.
[0022] The content of the sub-micro copper particles is preferably 20% by mass or more and 90% by mass or less based on the total mass of the copper particles. If the content of the sub-micro copper particles is 20% by mass or more, when used in combination with micro copper particles such as flake-shaped micro copper particles, the spaces between the copper particles can be sufficiently filled, and it is easy to ensure the bonding strength of the bonded body produced by sintering the bonding copper paste, and when the bonding copper paste is used for bonding a semiconductor element, the semiconductor device tends to exhibit good die shear strength and connection reliability. If the content of the sub-micro copper particles is 90% by mass or less, the volume shrinkage when the bonding copper paste is sintered without pressure can be sufficiently suppressed, so that it is easy to ensure the bonding strength of the bonded body produced by sintering the bonding copper paste, and when the bonding copper paste is used for bonding a semiconductor element, the semiconductor device tends to exhibit good die shear strength and connection reliability. From the viewpoint of further achieving the above-mentioned effect, the content of the submicro copper particles may be, based on the total mass of the copper particles, 30 mass% or more, 35 mass% or more, 40 mass% or more, 85 mass% or less, 83 mass% or less, 80 mass% or less, 30 mass% or more and 85 mass% or less, 35 mass% or more and 85 mass% or less, or 40 mass% or more and 80 mass% or less.
[0023] The shape of the submicro copper particles is not particularly limited. Examples of the shape of the submicro copper particles include spherical, clumpy, needle-like, flake-like, approximately spherical, and aggregates thereof. From the viewpoint of dispersibility and packing, the shape of the submicro copper particles may be spherical, approximately spherical, or flake-like, and from the viewpoint of combustibility, dispersibility, mixability with flake-like microparticles, etc., it may be spherical or approximately spherical. In this specification, the term "flake-like" includes flat shapes such as plate-like and scale-like.
[0024] From the viewpoints of dispersibility, packing property, and mixability with flake-shaped microparticles, the sub-micro copper particles may have an aspect ratio of 5 or less, 4 or less, or 3 or less. In this specification, the "aspect ratio" refers to the long side (major axis) / thickness of a particle. The long side (major axis) and thickness of a particle can be measured, for example, from an SEM image of the particle.
[0025] The sub-micro copper particles may be treated with a surface treatment agent, such as an organic acid having 2 to 18 carbon atoms.Examples of organic acids having 2 to 18 carbon atoms include acetic acid, propanoic acid, butanoic acid, pentanoic acid, hexanoic acid, heptanoic acid, caprylic acid, methylheptanoic acid, ethylhexanoic acid, propylpentanoic acid, pelargonic acid, methyloctanoic acid, ethylheptanoic acid, propylhexanoic acid, capric acid, methylnonanoic acid, ethyloctanoic acid, propylheptanoic acid, butylhexanoic acid, undecanoic acid, methyldecanoic acid, ethylnonanoic acid, propyloctanoic acid, butylheptanoic acid, dodecanoic acid (lauric acid), methylundecanoic acid, ethyldecanoic acid, propyl nonanoic acid, butyloctanoic acid, pentylheptanoic acid, tridecanoic acid, methyldodecanoic acid, ethylundecanoic acid, propyldecanoic acid, butylnonanoic acid, pentyloctanoic acid, myristic acid, methyltridecanoic acid, ethyldodecanoic acid, propylundecanoic acid, butyldecanoic acid, pentylnonanoic acid, hexyloctanoic acid, pentadecanoic acid, methyltetradecanoic acid, ethyltridecanoic acid, propyldodecanoic acid, butylundecanoic acid, pentyldecanoic acid, hexylnonanoic acid, palmitic acid, methylpentadecanoic acid, ethyltetradecanoic acid, proline Saturated fatty acids such as propyltridecanoic acid, butyldodecanoic acid, pentylundecanoic acid, hexyldecanoic acid, heptylnonanoic acid, heptadecanoic acid, octadecanoic acid (stearic acid), methylcyclohexanecarboxylic acid, ethylcyclohexanecarboxylic acid, propylcyclohexanecarboxylic acid, butylcyclohexanecarboxylic acid, pentylcyclohexanecarboxylic acid, hexylcyclohexanecarboxylic acid, heptylcyclohexanecarboxylic acid, octylcyclohexanecarboxylic acid, and nonylcyclohexanecarboxylic acid; octenoic acid, nonenoic acid, Examples of the organic acid include unsaturated fatty acids such as methylnonenoic acid, decenoic acid, undecenoic acid, dodecenoic acid, tridecenoic acid, tetradecenoic acid, myristoleic acid, pentadecenoic acid, hexadecenoic acid, palmitoleic acid, sapienic acid, oleic acid, vaccenic acid, linoleic acid, linolenic acid, and linolenic acid; and aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, o-phenoxybenzoic acid, methylbenzoic acid, ethylbenzoic acid, propylbenzoic acid, butylbenzoic acid, pentylbenzoic acid, hexylbenzoic acid, heptylbenzoic acid, octylbenzoic acid, and nonylbenzoic acid. The organic acid may be used alone or in combination of two or more.By combining such an organic acid with the sub-micron copper particles, it tends to be possible to achieve both the dispersibility of the sub-micron copper particles and the desorption property of the organic acid during sintering.
[0026] The amount of the surface treatment agent to be used may be an amount that allows one to three molecular layers to adhere to the surface of the sub-micro copper particles. This amount depends on the number of molecular layers (n) adhered to the surface of the sub-micro copper particles, the specific surface area (A p ) (unit: m 2 / g) and the molecular weight of the surface treatment agent (M s ) (unit: g / mol) and the minimum coverage area of the surface treatment agent (S S ) (unit: m 2 / piece) and Avogadro's number (N A )(6.02×10 23 Specifically, the amount of surface treatment agent can be calculated by the amount of surface treatment agent (mass%) = {(n·A p M s ) / (S S N A +n·A p M s )}×100%.
[0027] The specific surface area of submicro copper particles can be calculated by measuring the dried submicro copper particles using the BET specific surface area measurement method. The minimum coverage area of the surface treatment agent is 2.05 × 10 -19 m 2 The carbon content of the surface treatment agent is 1 / molecule. In the case of other surface treatment agents, it can be measured, for example, by calculation from a molecular model or by the method described in "Chemistry and Education" (Katsuhiro Ueda, Sumio Inafuku, Iwao Mori, 40(2), 1992, p114-117). An example of a method for quantifying the surface treatment agent is shown below. The surface treatment agent can be identified by a thermal desorption gas-gas chromatograph mass spectrometer of the dried powder obtained by removing the dispersing medium from the bonding copper paste, and the carbon number and molecular weight of the surface treatment agent can be determined. The carbon content of the surface treatment agent can be analyzed by carbon content analysis. Examples of carbon content analysis methods include high-frequency induction heating furnace combustion / infrared absorption method. The amount of the surface treatment agent can be calculated from the carbon number, molecular weight, and carbon content of the identified surface treatment agent using the above formula.
[0028] The amount of the surface treatment agent may be 0.07% by mass or more and 2.1% by mass or less, 0.10% by mass or more and 1.6% by mass or less, or 0.2% by mass or more and 1.1% by mass or less, based on the mass of the sub-micro copper particles having the surface treatment agent.
[0029] Submicro copper particles can be commercially available. Commercially available submicro particles include, for example, CH-0200L1 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.2 μm), CH-0200 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.36 μm), CH-0200A-L1 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.21 μm), HT-14 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.41 μm), CT-500 (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle diameter 0.72 μm), and Tn-Cu100 (manufactured by Taiyo Nippon Sanso Co., Ltd., volume average particle diameter 0.12 μm).
[0030] Submicro copper particles have good sinterability, which can reduce the problems associated with bonding materials that mainly use copper nanoparticles, such as high synthesis costs, poor dispersibility, and reduced volume shrinkage after sintering.
[0031] (Micro copper particles) As the micro copper particles, copper particles having a particle size of 2 μm to 50 μm can be used, for example, copper particles having a volume average particle size of 2 μm to 50 μm. If the volume average particle size of the micro copper particles is within the above range, the volume shrinkage and generation of voids when the bonding copper paste is sintered without pressure can be sufficiently reduced, and it is easy to ensure the bonding strength of the bonded body produced by sintering the bonding copper paste without pressure, and when the bonding copper paste is used for bonding a semiconductor element, the semiconductor device tends to exhibit good die shear strength and connection reliability. From the viewpoint of further achieving the above effect, the volume average particle size of the micro copper particles may be 2 μm to 20 μm, 2 μm to 10 μm, 3 μm to 20 μm, or 3 μm to 10 μm.
[0032] The shape of the micro copper particles is preferably flake-shaped. By using flake-shaped micro copper particles, the micro copper particles in the bonding copper paste are oriented approximately parallel to the bonding surface, so that the volume shrinkage when the bonding copper paste is sintered can be suppressed, and it is easy to ensure the bonding strength of the bonded body manufactured by sintering the bonding copper paste. When the bonding copper paste is used for bonding a semiconductor element, the semiconductor device tends to exhibit good die shear strength and connection reliability. From the viewpoint of further achieving the above effect, the flake-shaped micro copper particles may have an aspect ratio of 4 or more, 6 or more, 10 or more, or 50 or more.
[0033] The content of the micro copper particles may be 10% by mass or more, 15% by mass or more, 20% by mass or more, 90% by mass or less, 65% by mass or less, 60% by mass or less, 10% by mass or more and 90% by mass or less, 15% by mass or more and 65% by mass or less, or 20% by mass or more and 60% by mass or less, based on the total mass of the copper particles. If the content of the micro copper particles is within the above range, it is easy to ensure the bonding strength of the bonded body produced by sintering the bonding copper paste, and when the bonding copper paste is used for bonding a semiconductor element, the semiconductor device tends to exhibit good die shear strength and connection reliability.
[0034] In the micro copper particles, the presence or absence of treatment with a surface treatment agent is not particularly limited, but from the viewpoint of dispersion stability and oxidation resistance, the micro copper particles may be treated with a surface treatment agent. The surface treatment agent may be one that is removed during bonding. Examples of such surface treatment agents include aliphatic carboxylic acids such as dodecanoic acid (lauric acid), palmitic acid, heptadecanoic acid, octadecanoic acid (stearic acid), arachidic acid, linoleic acid, linoleic acid, and oleic acid; aromatic carboxylic acids such as terephthalic acid, pyromellitic acid, and o-phenoxybenzoic acid; aliphatic alcohols such as cetyl alcohol, stearyl alcohol, isobornylcyclohexanol, and tetraethylene glycol; aromatic alcohols such as p-phenylphenol; alkylamines such as octylamine, dodecylamine, and stearylamine; aliphatic nitriles such as stearonitrile and decanenitrile; silane coupling agents such as alkylalkoxysilanes; and polymer treatment agents such as polyethylene glycol, polyvinyl alcohol, polyvinylpyrrolidone, and silicone oligomers. The surface treatment agent may be used alone or in combination of two or more kinds.
[0035] The amount of the surface treatment agent may be more than one molecular layer on the particle surface. The amount of the surface treatment agent varies depending on the specific surface area of the micro copper particles, the molecular weight of the surface treatment agent, and the minimum coverage area of the surface treatment agent. The amount of the surface treatment agent may be 0.001% by mass or more, 0.4% by mass or more, 0.5% by mass or more, 2.0% by mass or less, 1.7% by mass or less, 0.001% by mass or more and 2.0% by mass or less, 0.4% by mass or more and 2.0% by mass or less, or 0.5% by mass or more and 1.7% by mass or less, based on the mass of the micro copper particles having the surface treatment agent. The specific surface area of the micro copper particles, the molecular weight of the surface treatment agent, and the minimum coverage area of the surface treatment agent can be calculated by the same method as in the case of the sub-micro copper particles described above.
[0036] Micro copper particles can be commercially available. Examples of commercially available flake-shaped micro particles include MA-05KFD (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 8 μm), MA-C025KFD (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 7.5 μm), 3L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 6 μm), 2L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 9.9 μm), 4L3N (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 3 μm), C3 (manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size 37 μm), and 1110F (manufactured by Mitsui Mining & Smelting Co., Ltd., volume average particle size 3.8 μm). Examples of commercially available spherical micro particles include FMC-10 (manufactured by Furukawa Chemicals Co., Ltd., volume average particle size 2 μm).
[0037] The bonding copper paste according to the present embodiment can contain sub-micro copper particles and micro copper particles. When the bonding copper paste is prepared only from the sub-micro copper particles, the volume shrinkage and sintering shrinkage accompanying drying of the dispersion medium are large, so that the bonding copper paste is easily peeled off from the adherend surface during sintering, and it is difficult to obtain sufficient die shear strength and connection reliability in bonding of semiconductor elements and the like. When the bonding copper paste is prepared only from the micro copper particles, the sintering temperature tends to be high, and a sintering process of 400°C or more is required. By using the sub-micro copper particles and the micro copper particles in combination, the volume shrinkage when the bonding copper paste is sintered is suppressed, and the bonded body can have sufficient bonding strength. When the bonding copper paste is used for bonding of semiconductor elements, the effect of the semiconductor device exhibiting good die shear strength and connection reliability can be obtained.
[0038] From the above viewpoint, the copper paste for bonding according to this embodiment contains, as copper particles, sub-micro copper particles having a volume average particle size of 0.15 μm or more and 0.8 μm or less, and micro copper particles having a volume average particle size of 2 μm or more and 50 μm or less, and the sum of the content of the sub-micro copper particles and the content of the micro copper particles is 80 mass % or more based on the total mass of the metal particles, and the content of the sub-micro copper particles may be 30 mass % or more, 90 mass % or less, or 30 mass % or more and 90 mass % or less based on the sum of the mass of the sub-micro copper particles and the mass of the micro copper particles.
[0039] The bonding copper paste according to this embodiment may contain sub-micro copper particles, flaky micro copper particles, and spherical micro copper particles from the viewpoints of low-temperature sintering, suppression of volumetric shrinkage in the XY directions (directions parallel to the bonding surface), and improving the filling of the copper particles.
[0040] (Metal particles other than copper particles) The bonding metal paste of the present embodiment may contain metal particles (other metal particles) containing a metal element other than copper as the metal particles. The other metal particles may contain, for example, particles of zinc, gold, palladium, silver, nickel, platinum, brass, manganese, tin, antimony, indium, aluminum, vanadium, etc. The volume average particle size of the other metal particles may be 0.01 μm or more, 0.03 μm or more, 0.05 μm or more, 10 μm or less, 5 μm or less, 3 μm or less, 0.01 μm or more and 10 μm or less, 0.01 μm or more and 5 μm or less, or 0.05 μm or more and 3 μm or less.
[0041] When the bonding copper paste contains other metal particles, a sintered body in which multiple metals are dissolved or dispersed can be obtained, improving mechanical properties such as yield stress and fatigue strength of the sintered body and improving connection reliability. In addition, by adding multiple metal particles, the sintered body of the bonding copper paste can have sufficient bonding strength to a specific adherend. When the bonding copper paste is used to bond a semiconductor element, the die shear strength and connection reliability of the semiconductor device are likely to be improved.
[0042] When the bonding copper paste contains other metal particles, the content of the other metal particles may be less than 5 mass%, 3 mass% or less, or 1 mass% or less based on the total mass of the metal particles from the viewpoint of obtaining sufficient bonding properties. The bonding copper paste may not contain other metal particles. The shape of the other metal particles is not particularly limited.
[0043] In the metal paste for bonding of this embodiment, the metal particles may be surface-treated with a fatty acid having 12 to 18 carbon atoms. The fatty acid having 12 to 18 carbon atoms may be dodecanoic acid (lauric acid) or octadecanoic acid (stearic acid), and one type may be used alone or two or more types may be used in combination. When the metal paste for bonding of this embodiment contains the above-mentioned sub-micro copper particles and micro copper particles as the metal particles, these copper particles may be surface-treated with a fatty acid having 12 to 18 carbon atoms.
[0044] Since the surfaces of metal particles that have been subjected to the above-mentioned surface treatment are highly hydrophobic, it is thought that the repulsion with the water-absorbed PEG will be stronger (making solvent separation more likely to occur). However, by incorporating the above-mentioned compound A, the particle surface can be made partially hydrophilic, making it possible to suppress the occurrence of solvent separation even in a high humidity environment.
[0045] The bonding metal paste of the present embodiment may have a content of inorganic particles other than metal particles of 30 mass % or less, 20 mass % or less, or 1 mass % or less based on the total amount of the bonding metal paste. The bonding copper paste may not contain inorganic particles other than metal particles.
[0046] [Reducing agent] The copper bonding paste contains polyethylene glycol as a reducing agent.
[0047] Examples of polyethylene glycol include polyethylene glycol 200, polyethylene glycol 300, and polyethylene glycol 400. These may be used alone or in combination of two or more.
[0048] The bonding copper paste may contain polyethylene glycol 200 from the viewpoints of volatilization behavior and timing of onset of reducing properties.
[0049] The content of polyethylene glycol in the copper paste for bonding may be 1 to 10 parts by mass relative to 100 parts by mass of the total mass of the copper particles from the viewpoint of suppressing poor sintering and ensuring bonding strength, and may be 5 parts by mass or less from the viewpoint of suppressing a decrease in bonding strength due to an excess of reducing agent.
[0050] When the bonding copper paste contains copper particles and other metal particles, the content of polyethylene glycol may be within the above-mentioned range with respect to 100 parts by mass of the total mass of the metal particles. Examples of the other metal particles include particles of zinc, gold, palladium, silver, nickel, platinum, brass, manganese, tin, antimony, indium, aluminum, vanadium, etc.
[0051] The bonding copper paste may further contain a reducing agent other than polyethylene glycol. Examples of such reducing agents include diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, hexaethylene glycol, dipropylene glycol, tripropylene glycol, tetrapropylene glycol, polypropylene glycol, polypropylene glycol 200, polypropylene glycol 300, polypropylene glycol 400, polypropylene glycol 700, polypropylene glycol 4000, polyethylene glycol monooleate, polyethylene glycol monostearate, polyethylene glycol monolaurate, polyoxyethylene sorbitan monolaurate, polyoxyethylene polyoxypropylene glycol, etc. These may be used alone or in combination of two or more.
[0052] The content of the reducing agent in the copper paste for bonding may be 1.6 parts by mass or more, 1.8 parts by mass or more, 2.0 parts by mass or more, or 4.0 parts by mass or more, relative to 100 parts by mass of the total mass of the copper particles, from the viewpoint of suppressing poor sintering and ensuring bonding strength, and may be 10 parts by mass or less, 9.0 parts by mass or less, or 8.5 parts by mass or less, from the viewpoint of suppressing a decrease in bonding strength due to an excess of the reducing agent.
[0053] In addition, when the bonding copper paste contains copper particles and other metal particles, the content of the reducing agent may be in the above-mentioned range with respect to 100 parts by mass of the total mass of the metal particles. Examples of the other metal particles include particles of zinc, gold, palladium, silver, nickel, platinum, brass, manganese, tin, antimony, indium, aluminum, vanadium, etc.
[0054] [Dispersion medium] Examples of the dispersion medium include monohydric and polyhydric alcohols such as pentanol, hexanol, heptanol, octanol, decanol, dihydroterpineol, terpineol, and isobornylcyclohexanol (MTPH); ethylene glycol butyl ether, ethylene glycol phenyl ether, diethylene glycol methyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, diethylene glycol isobutyl ether, diethylene glycol hexyl ether, triethylene glycol methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, diethylene glycol isopropyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, propylene glycol propyl ether, dipropylene glycol methyl ether, dipropylene glycol dimethyl ether, dipropylene glycol methyl ether, dipropylene glycol hexyl ether, triethylene glycol dimethyl ether, diethylene glycol propyl ether, dipropylene ... ethers such as ethylene glycol ethyl ether, dipropylene glycol propyl ether, dipropylene glycol butyl ether, dipropylene glycol dimethyl ether, tripropylene glycol methyl ether, and tripropylene glycol dimethyl ether; esters such as ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dipropylene glycol methyl ether acetate (DPMA), ethyl lactate, butyl lactate, γ-butyrolactone, and propylene carbonate; acid amides such as N-methyl-2-pyrrolidone, N,N-dimethylacetamide, and N,N-dimethylformamide; aliphatic hydrocarbons such as cyclohexanone, octane, nonane, decane, and undecane; aromatic hydrocarbons such as benzene, toluene, and xylene; mercaptans having an alkyl group having 1 to 18 carbon atoms; and mercaptans having a cycloalkyl group having 5 to 7 carbon atoms.Examples of mercaptans having an alkyl group having 1 to 18 carbon atoms include ethyl mercaptan, n-propyl mercaptan, i-propyl mercaptan, n-butyl mercaptan, i-butyl mercaptan, t-butyl mercaptan, pentyl mercaptan, hexyl mercaptan, and dodecyl mercaptan. Examples of mercaptans having a cycloalkyl group having 5 to 7 carbon atoms include cyclopentyl mercaptan, cyclohexyl mercaptan, and cycloheptyl mercaptan.
[0055] From the viewpoint of printing life (on-plate life), the dispersion medium may contain a solvent having a boiling point of 140° C. or higher, may contain a solvent having a boiling point of 170° C. or higher, or may contain a solvent having a boiling point of 200° C. or higher. In addition, the boiling point of the solvent may be 400° C. or lower, 380° C. or lower, or 360° C. or lower, since it must be removed after sintering.
[0056] The dispersion medium may be used alone or in combination of two or more kinds.
[0057] [Compound A] Compound A has, in the molecule, at least one group selected from the group consisting of an amino group, a carboxyl group, and an acetylene group, and a hydroxyl group.
[0058] Examples of the compound A include triethanolamine, diethanolamine, monoethanolamine, hydroxyacetic acid, and acetylene alcohol surfactants. The compound A can be used alone or in combination of two or more.
[0059] The acetylene alcohol surfactant may be an acetylene glycol compound represented by the following general formula (A-1).
[0060] [ka] [In formula (A-1), R 1and R 2 represents a hydrocarbon group having 6 to 12 carbon atoms, and L 1 and L 2 represents an ethylene group or a propylene group, and n and m represent integers of 0 or 1 or more. 1 and R 2 may be the same or different. 1 and L 2 may be the same or different.]
[0061] The acetylene glycol compound represented by the general formula (A-1) may be acetylene glycol or an acetylene glycol alkylene oxide adduct. Examples of acetylene glycol include 5,8-dimethyl-6-dodecyne-5,8-diol, 4,7-dimethyl-5-decyne-4,7-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2,3,6,7-tetramethyl-4-octyne-3,6-diol, 3,6-dimethyl-4-octyne-3,6-diol, 3,6-diethyl-4-octyne-3,6-diol, and 2,5-dimethyl-3-hexyne-2,5-diol.
[0062] The acetylene glycol alkylene oxide adduct can be obtained by converting the acetylene glycol into an alkylene oxide. The average number of moles of alkylene oxide added may be 1 to 6.
[0063] As the acetylene alcohol surfactant, commercially available products such as "Acetylenol E00", "Acetylenol E40", and "Acetylenol E13T" (all of which are product names manufactured by Kawasaki Fine Chemical Co., Ltd.) and "Olfine" (product name manufactured by Nissin Chemical Industry Co., Ltd.) may be used.
[0064] The content of compound A in the copper paste for bonding may be 0.5 to 5 parts by mass relative to 100 parts by mass of the total mass of the copper particles from the viewpoint of suppressing solvent separation, and may be 3 parts by mass or less from the viewpoint of suppressing a decrease in bonding strength due to excess compound A.
[0065] In addition, when the copper paste for bonding contains copper particles and other metal particles, the content of compound A may be in the above-mentioned range with respect to 100 parts by mass of the total mass of the metal particles.
[0066] [Additives] The bonding metal paste may further contain additives such as a dispersant, a surface protective agent, a thickener, and a thixotropy imparting agent, if necessary.
[0067] When the joining metal paste contains an additive, in order to suppress a decrease in the sinterability of the joining metal paste, the content of the additive that is non-volatile or non-decomposable at a temperature of 200°C or less may be 20 mass% or less, 5 mass% or less, or 1 mass% or less, based on the total amount of the joining metal paste.
[0068] <Method of preparing metal paste for bonding> The bonding metal paste of this embodiment can be prepared by mixing the above-mentioned copper particles (e.g., submicro copper particles and micro copper particles), a reducing agent (e.g., PEG), a dispersion medium, and, if necessary, other metal particles and any additives. After mixing the components, a stirring process may be performed. The bonding metal paste may be classified to adjust the maximum particle size of the dispersion.
[0069] The bonding metal paste may be prepared by previously mixing sub-micro copper particles, an organic protective agent (e.g., fatty acid having 12 to 18 carbon atoms), a reducing agent (e.g., PEG), and a dispersion medium, dispersing the mixture to prepare a dispersion of sub-micro copper particles, and then mixing the remaining components. By using such a procedure, the dispersibility of the sub-micro copper particles is improved, and the mixture with the micro-copper particles (e.g., flake-shaped micro-copper particles) is improved, and the performance of the bonding copper paste can be further improved. In addition, aggregates may be removed from the dispersion of the sub-micro copper particles by a classification operation. The sub-micro copper particles and the organic protective agent may be sub-micro copper particles treated with an organic protective agent.
[0070] The stirring treatment can be carried out using a stirrer, such as an Ishikawa stirrer, a Silverson stirrer, a cavitation stirrer, a rotation-revolution type stirrer, an ultra-thin film high-speed rotary disperser, an ultrasonic disperser, a Raikai machine, a twin-screw kneader, a bead mill, a ball mill, a three-roll mill, a homomixer, a planetary mixer, an ultra-high pressure type disperser, a thin layer shear disperser, or a dispersizer.
[0071] Examples of the dispersion treatment include a thin layer shear disperser, a dispersizer, a bead mill, an ultrasonic homogenizer, a high shear mixer, a narrow gap three-roll mill, a wet type ultra-atomizer, a supersonic jet mill, and an ultra-high pressure homogenizer.
[0072] The classification can be carried out, for example, by filtration, natural sedimentation, or centrifugation. Examples of filters for filtration include water combs, metal meshes, metal filters, and nylon meshes.
[0073] The bonding copper paste may be adjusted to a viscosity suitable for the printing / coating method. The viscosity of the bonding copper paste may be, for example, a Casson viscosity at 25°C of 0.05 Pa·s or more, 0.06 Pa·s or more, 2.0 Pa·s or less, 1.0 Pa·s or less, 0.05 Pa·s or more to 2.0 Pa·s or less, or 0.06 Pa·s or more to 1.0 Pa·s or less. The Casson viscosity at 25°C can be measured using a viscoelasticity measuring device.
[0074] <Method of manufacturing the bonded body> The manufacturing method of the joint body according to this embodiment includes a laminate preparation process for preparing a laminate in which a first member, the joining metal paste according to this embodiment described above, and a second member are stacked in this order, and a sintering process for sintering the joining metal paste in the laminate.
[0075] (Laminate preparation process) Examples of the first member and the second member include semiconductor elements such as IGBTs, diodes, Schottky barrier diodes, MOS-FETs, thyristors, logic, sensors, analog integrated circuits, LEDs, semiconductor lasers, and oscillators, base materials for mounting semiconductor elements such as lead frames, metal plate-attached ceramic substrates (e.g., DBC), and LED packages, power supply members such as copper ribbons, metal blocks, and terminals, heat sinks, and water-cooled plates.
[0076] The first member and the second member may have a metal layer on the joining surface that forms a metal bond with the sintered body of the joining metal paste. Examples of metals constituting the metal layer include copper, nickel, silver, gold, palladium, platinum, lead, tin, cobalt, etc. These metals may be used alone or in combination of two or more. The metal layer may also be an alloy containing the above metals. In addition to the above metals, examples of metals used in the alloy include zinc, manganese, aluminum, beryllium, titanium, chromium, iron, molybdenum, etc. Examples of members having a metal layer include members having various metal platings, wires, chips having metal platings, heat spreaders, ceramic substrates to which metal plates are attached, lead frames having various metal platings or lead frames made of various metals, copper plates, and copper foils.
[0077] The laminate can be prepared, for example, by providing the bonding metal paste of this embodiment on a necessary portion of the above-mentioned second member, and then placing the above-mentioned first member on the bonding metal paste. In this case, a laminate can be prepared in which the first member, the bonding metal paste, and the second member are laminated in this order on the side in which the weight of the first member acts, and the bonding metal paste of this laminate can be sintered without pressure, that is, under the weight of only the first member, or the weight of the first member and the weight of a weight used to prevent the chip from tilting or reduce voids. The weight of the weight may be 0.01 MPa or less when converted into pressure. The direction in which the weight of the first member acts can also be said to be the direction in which gravity acts.
[0078] The weight may be a metal weight having a size similar to that of the chip and a thickness of 20 mm or less, such as a SUS weight having a thickness of 5 mm or less.
[0079] The method for providing the bonding metal paste of this embodiment on the necessary portion of the second member may be any method capable of depositing the bonding copper paste, such as inkjet printing, super inkjet printing, screen printing, transfer printing, offset printing, jet printing, dispenser, jet dispenser, needle dispenser, comma coater, slit coater, die coater, gravure coater, slit coat, letterpress printing, intaglio printing, gravure printing, stencil printing, soft lithography, bar coat, applicator, particle deposition method, spray coater, spin coater, dip coater, electrochemical coating, etc.
[0080] The thickness of the bonding metal paste may be 1 μm or more, 5 μm or more, 10 μm or more, or 20 μm or more. Also, the thickness of the bonding metal paste may be 3000 μm or less, 1000 μm or less, 500 μm or less, 300 μm or less, 250 μm or less, 200 μm or less, or 150 μm or less.
[0081] The applied bonding metal paste may be dried appropriately from the viewpoint of suppressing flow and generation of voids during sintering. The gas atmosphere during drying may be air, an oxygen-free atmosphere such as nitrogen or a rare gas, or a reducing atmosphere such as hydrogen or formic acid. The drying method may be drying by leaving at room temperature, drying by heating, or drying under reduced pressure.
[0082] For drying by heating or drying under reduced pressure, for example, a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, a hot plate press device, etc. can be used. The drying temperature and time may be appropriately adjusted according to the type and amount of the dispersion medium used. As for the drying temperature and time, it is desirable to dry in the air or in an oxygen-free atmosphere at 50°C or higher and 150°C or lower.
[0083] The first member may be placed on the bonding metal paste by, for example, using a chip mounter, a flip chip bonder, or a positioning jig made of carbon or ceramics.
[0084] (Sintering process) In the sintering step, the bonding copper paste can be sintered by heat treatment in an oxygen-free atmosphere without pressure. The oxygen-free atmosphere may be an atmosphere that does not contain hydrogen or has a hydrogen concentration of 10% or less. The oxygen-free atmosphere refers to an atmosphere with an oxygen concentration of 1% by volume or less, and the oxygen concentration may be 0.1% by volume or less, 0.01% by volume or less, or 0.001% by volume or less.
[0085] For the heat treatment, a heating device without a pressure bonding mechanism can be used, such as a hot plate, a hot air dryer, a hot air heating furnace, a nitrogen dryer, an infrared dryer, an infrared heating furnace, a far-infrared heating furnace, a microwave heating device, a laser heating device, an electromagnetic heating device, a heater heating device, a steam heating furnace, etc.
[0086] The hydrogen-free atmosphere may be a non-oxidizing gas such as nitrogen, a rare gas, a heat-resistant organic gas, water vapor, or a mixture of these, or may be under vacuum.
[0087] The gas atmosphere during sintering may be a reducing atmosphere. Examples of the reducing atmosphere include nitrogen containing formic acid gas, rare gas containing formic acid gas, and non-oxidizing gas containing 10% or less hydrogen. The gas atmosphere during sintering may be forming gas (nitrogen containing hydrogen below the lower explosion limit (e.g., 5% or less or 3% or less)) or low molecular weight alcohol (e.g., methanol, ethanol) vapor.
[0088] The maximum temperature reached during the heat treatment may be 200°C or more, 220°C or more, or 250°C or more from the viewpoint of improving the yield, and may be 450°C or less, 400°C or less, 350°C or less, or 300°C or less from the viewpoint of reducing thermal damage to the members to be joined, and may be 200°C or more and 450°C or less, 250°C or more and 400°C or less, 250°C or more and 350°C or less, or 250°C or more and 300°C or less from the viewpoint of reducing thermal damage to the members to be joined and improving the yield.
[0089] The maximum temperature holding time may be 1 minute or more and 60 minutes or less, or 1 minute or more and less than 40 minutes, or 1 minute or more and less than 30 minutes, from the viewpoint of volatilizing all of the dispersion medium and improving the yield. In particular, when the maximum temperature to be reached is 250°C or more, sintering tends to proceed sufficiently with a holding time of 60 minutes or less.
[0090] <Joint body and semiconductor device> Hereinafter, preferred embodiments will be described in detail with reference to the drawings. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. Furthermore, the dimensional ratios of the drawings are not limited to those shown in the drawings.
[0091] 1 is a schematic cross-sectional view showing an example of a bonded body produced using a bonding metal paste. The bonded body 100 of this embodiment includes a first member 1 having a first base 1a and a first metal layer 1b, a second member 3 having a second base 3a and a second metal layer 3b, and a sintered body 2 bonding the first member 1 and the second member 3 together.
[0092] The same can be mentioned above for the first member 1 and the second member 3. The same can be mentioned above for the first metal layer 1b and the second metal layer 3b.
[0093] The sintered body 2 may be a sintered body of the bonding metal paste according to this embodiment. In this case, the bonded body 100 can be obtained by the manufacturing method of the bonded body according to this embodiment described above.
[0094] From the viewpoint of sufficiently bonding the first member and the second member, the die shear strength of the bonded body may be 10 MPa or more, 15 MPa or more, 20 MPa or more, or 30 MPa or more. The die shear strength can be measured using a universal bond tester (4000 series, manufactured by DAGE Co., Ltd.) or the like.
[0095] From the viewpoint of heat dissipation and connection reliability at high temperatures, the thermal conductivity of the sintered body may be 100 W / (m K) or more, 120 W / (m K) or more, or 150 W / (m K) or more. The thermal conductivity can be calculated from the thermal diffusivity, specific heat capacity, and density of the sintered body of the bonding metal paste.
[0096] In the above-mentioned bonded body, at least one of the first member and the second member may be a semiconductor element. Examples of the semiconductor element include a power module including a diode, a rectifier, a thyristor, a MOS gate driver, a power switch, a power MOSFET, an IGBT, a Schottky diode, a fast recovery diode, etc., a transmitter, an amplifier, an LED module, etc. In such a case, the above-mentioned bonded body becomes a semiconductor device. The obtained semiconductor device can have sufficient die shear strength and connection reliability.
[0097] Fig. 2 is a schematic cross-sectional view showing an example of a semiconductor device manufactured using a bonding metal paste. The semiconductor device 200 shown in Fig. 2 includes a semiconductor element 4 having a metal layer 4b and a base 4a connected via a sintered body 2 of the bonding copper paste on a lead frame 5 having a metal layer 5b and a base 5a, and a mold resin 6 for molding them. The semiconductor element 4 is connected via a wire 7 to a lead frame 8 having a metal layer 8b and a base 8a.
[0098] Examples of semiconductor devices include power modules consisting of diodes, rectifiers, thyristors, MOS gate drivers, power switches, power MOSFETs, IGBTs, Schottky diodes, fast recovery diodes, etc., transmitters, amplifiers, high-brightness LED modules, semiconductor laser modules, logic, sensors, etc.
[0099] The semiconductor device can be manufactured in the same manner as the manufacturing method of the bonded body according to the present embodiment described above. That is, the manufacturing method of the semiconductor device may include a step of using a semiconductor element for at least one of the first member and the second member, preparing a laminate in which the first member, the bonding metal paste, and the second member are laminated in this order, and heating the laminate in an oxygen-free atmosphere without pressure, thereby sintering the bonding metal paste. The oxygen-free atmosphere may be an atmosphere that does not contain hydrogen or has a hydrogen concentration of 10% or less.
[0100] The bonding metal paste may have the same composition as the bonding metal paste according to the present embodiment. Preparation of the laminate and sintering of the bonding metal paste can be performed in the same manner as the above-mentioned laminate preparation step and sintering step. EXAMPLES
[0101] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0102] [Preparation of metal paste for bonding] The bonding metal pastes having the amounts (parts by mass) shown in Table 1 were prepared according to the procedure described below.
[0103] Example 1 At room temperature (25°C) and a humidity of 60%, 9 g of dihydroterpineol (manufactured by Nippon Terpene Chemical Co., Ltd.) as a dispersion medium and 91 g of CH-0200L1 (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, volume average particle size 0.2 μm) as submicron copper particles were mixed and stirred for 30 minutes at a rotation speed of 300 rpm using a planetary mixer (manufactured by Primix Co., Ltd.). The resulting mixture was dispersed once using a dispersizer (manufactured by Shinto Kogyo Co., Ltd.) under conditions of a gap of 50 μm and a rotation speed of 12,000 rpm to obtain a 91% by mass dispersion.
[0104] As the remaining dispersion medium, 3 g of dihydroterpineol and 6 g of isobornylcyclohexanol (MTPH), 4 g of polyethylene glycol 200 (hereinafter abbreviated as PEG200) (manufactured by NOF Corporation) as a reducing agent, 1 g of triethanolamine as compound A, 62 g of the 91 mass% dispersion obtained above, and 12 g of MA-05KFD (manufactured by Mitsui Mining & Smelting Co., Ltd., product name, volume average particle size 8 μm) and 12 g of FMC-10 (manufactured by Furukawa Chemicals Corporation, product name, volume average particle size 2 μm) as micro copper particles were mixed and stirred at 2000 rpm under reduced pressure for 3 minutes in a planetary centrifugal mixer (manufactured by Thinky, Awatori Rentaro ARE-310) to obtain a metal paste for joining.
[0105] (Examples 2 to 7) As shown in Table 1, the bonding metal pastes were obtained in the same manner as in Example 1, except that diethanolamine, monoethanolamine, hydroxyacetic acid, Acetylenol E40 (product name, manufactured by Kawaken Fine Chemicals Co., Ltd.), Acetylenol E00 (product name, manufactured by Kawaken Fine Chemicals Co., Ltd.), and Acetylenol E13T (product name, manufactured by Kawaken Fine Chemicals Co., Ltd.) were used instead of triethanolamine as compound A.
[0106] Comparative Example 1 A metal bonding paste was obtained in the same manner as in Example 1, except that triethanolamine was not added.
[0107] [Evaluation of metal paste for joining-1] Using the bonding metal pastes obtained in the examples and comparative examples, bonded bodies were produced in a high humidity environment according to the following method, and the coating film was evaluated for "solvent separation" and "appearance" as well as die shear strength. The results are shown in the table.
[0108] Using an automatic printer "LZ-0913" (product name, manufactured by Newlong Co., Ltd.) and a stainless steel stencil mask with a thickness of 100 μm and an opening dimension of 12.6 mm × 11.4 mm, the metal paste was applied by stencil printing onto a copper plate (30 mm × 30 mm × 2 mm). The printing pressure (air pressure) against the squeegee was 0.08 MPa. Next, the coating film was left for 0.5 hours in an environment with a humidity of 70% or more, and then visually observed and evaluated according to the following criteria. (Solvent separation criteria) A: No droplets are formed on the surface B: Droplets are appearing on the surface (Appearance criteria) A: No droplets B: There are droplets
[0109] After observing the coating, a copper chip (area 2mm x 2mm, thickness 0.4mm) was placed on the applied metal paste to obtain a laminate. The laminate was heated at 90°C for 30 minutes in air on a hot plate (manufactured by AS ONE Corporation, EC HOTPLATE EC-1200N). The laminate was set in a bonding device (manufactured by Ayumi Industries Co., Ltd.), and the pressure was reduced to 13 Pa to remove the air. The laminate was then pressurized and heated to bond at a temperature of 260°C, a pressure of 10 MPa, and pressure bonding for 5 minutes while flowing nitrogen gas to an atmospheric pressure of 80 kPa, to obtain a bonded body in which the copper plate and the copper chip were bonded with a copper sintered body. The bonded body was cooled with nitrogen gas, and when it became 50°C or less, it was taken out into the air.
[0110] Next, a universal bond tester (4000 series, manufactured by DAGE) equipped with a 1kN load cell was used to press the copper chip horizontally at a measurement speed of 300μm / s and a measurement height of 50μm to measure the maximum load. For the measurement, a sample with 12 copper chips bonded to it was prepared (N=11), and the die shear strength was calculated by dividing the average value of the maximum load by the chip area.
[0111] [Evaluation of metal paste for joining-2] The bonding metal pastes obtained in the examples and comparative examples were stored for 1 hour in an environment with a humidity of 70% or more.
[0112] The metal paste for bonding after storage was used to prepare a bonded body according to the following method, and the coating film was evaluated for "solvent separation" and "appearance" as well as die shear strength in the same manner as described above. The results are shown in the table.
[0113] Using an automatic printer "LZ-0913" (product name, manufactured by Newlong Co., Ltd.) and a stainless steel stencil mask with a thickness of 100 μm and an opening dimension of 12.6 mm × 11.4 mm, the metal paste was applied by stencil printing onto a copper plate (30 mm × 30 mm × 2 mm). The printing pressure (air pressure) against the squeegee was 0.08 MPa. The coating film was visually observed and evaluated in the same manner as above.
[0114] After observing the coating film, a bonded body was obtained in the same manner as above. The die shear strength of the bonded body obtained was evaluated in the same manner as above.
[0115] [Table 1]
[0116] (Examples 8 to 11 and Comparative Example 2) Each of the bonding metal pastes was obtained in the same manner as in Examples 1, 5 to 7 and Comparative Example 1, except that the preparation was performed in an environment with a humidity of 70% or more.
[0117] [Evaluation of metal paste for joining-3]
[0118] Using the stored metal paste for bonding, a bonded body was produced according to the following method, and the "printability", "solvent separation" and "appearance" of the coating film, and the die shear strength were evaluated. The results are shown in the table.
[0119] Using an automatic printer "LZ-0913" (product name, manufactured by Newlong Co., Ltd.) and a stainless steel stencil mask with a thickness of 100 μm and an opening dimension of 12.6 mm × 11.4 mm, the metal paste was applied by stencil printing onto a copper plate (30 mm × 30 mm × 2 mm). The printing pressure (air pressure) against the squeegee was 0.08 MPa. The printability at this time was evaluated according to the following criteria. (Printability criteria) A: No streaks or clumps after printing B: Streaks or aggregates may be present after printing, and the base may be visible.
[0120] The coating film was also visually observed and evaluated in the same manner as above.
[0121] After observing the coating film, a bonded body was obtained in the same manner as above. The die shear strength of the bonded body obtained was evaluated in the same manner as above.
[0122] [Table 2] [Explanation of symbols]
[0123] 1...first member, 1a...first base, 1b...first metal layer, 2...sintered body, 3...second member, 3a...second base, 3b...second metal layer, 4...semiconductor element, 4a...base of semiconductor element, 4b...metal layer of semiconductor element, 5...lead frame, 5a...base, 5b...metal layer, 6...mold resin, 7...wire, 8...lead frame, 8a...base, 8b...metal layer, 100...joint, 200...semiconductor device.
Claims
1. A metal paste for bonding containing metal particles, a dispersion medium, and a reducing agent, The reducing agent includes polyethylene glycol, A metal bonding paste comprising a compound A having, in its molecule, at least one group selected from the group consisting of an amino group, a carboxyl group and an acetylene group, and a hydroxyl group.
2. The metal paste for joining according to claim 1, wherein the metal particles are fatty acids having 12 to 18 carbon atoms.
3. The metal paste for bonding according to claim 1 , wherein the compound A comprises at least one selected from the group consisting of triethanolamine, diethanolamine, monoethanolamine, hydroxyacetic acid, and an acetylene alcohol-based surfactant.
4. The bonding metal paste according to claim 1 , wherein the metal particles include sub-micro copper particles having a volume average particle size of 0.01 μm or more and 0.8 μm or less, and micro copper particles having a volume average particle size of 2 μm or more and 50 μm or less.
5. The bonding metal paste according to claim 4 , wherein the micro copper particles are in a flake shape.
6. A step of preparing a laminate in which a first member, the metal paste for bonding according to any one of claims 1 to 5, and a second member are laminated in this order; a sintering step of sintering the bonding metal paste in the laminate; A method for manufacturing a bonded body comprising the steps of:
7. The method for producing a bonded body according to claim 6 , wherein at least one of the first member and the second member is a semiconductor element.
8. A joined body comprising a first member, a second member, and a sintered body of the joining metal paste according to any one of claims 1 to 5, which joins the first member and the second member.
Citation Information
Patent Citations
JP1975006081A
Sinterable metal particle composition having plasticity, manufacturing method thereof, bonding agent, and bonding method
JP4247800B2
Cited By
Copper paste for joining, method for manufacturing copper paste for joining, and method for manufacturing a joined body
JP7928665B1
Metal paste for joining, and joined body and method for producing same
WO2026163353A1